2005
DOI: 10.1521/pedi.2005.19.5.505
|View full text |Cite
|
Sign up to set email alerts
|

The McLean Study of Adult Development (MSAD): Overview and Implications of the First Six Years of Prospective Follow-Up

Abstract: The McLean Study of Adult Development (MSAD) began 12 years ago. It is the first NIMH-funded prospective study of the course and outcome of borderline personality disorder (BPD). After careful analysis of the first six years of follow-up, 5 main findings concerning the symptomatic and psychosocial course of BPD have emerged from this study. The first finding is that remissions are far more common than previously recognized (about 74%). The second is that these remissions are quite stable and thus, recurrences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
223
1
17

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(250 citation statements)
references
References 12 publications
9
223
1
17
Order By: Relevance
“…The symptom items, worded in non-technical language to avoid the need for insight or judgment, were adapted to be fully structured from items in the Structured Clinical Interview for DSM-IV Personality Disorders 65 , International Personality Disorder Examination 66 , and Diagnostic Interview for DSM-IV Personality Disorders 62 . AUDADIS-IV reliability, assessed in test-retest studies of NESARC participants 37, 38 , ranged from fair (paranoid, histrionic, avoidant κ=0.40-0.45) to very good (schizotypal, antisocial, narcissistic, borderline κ=0.67-0.71) 37, 38 , comparing favorably with semi-structured interviews in clinical samples 67 .…”
Section: Methodsmentioning
confidence: 99%
“…The symptom items, worded in non-technical language to avoid the need for insight or judgment, were adapted to be fully structured from items in the Structured Clinical Interview for DSM-IV Personality Disorders 65 , International Personality Disorder Examination 66 , and Diagnostic Interview for DSM-IV Personality Disorders 62 . AUDADIS-IV reliability, assessed in test-retest studies of NESARC participants 37, 38 , ranged from fair (paranoid, histrionic, avoidant κ=0.40-0.45) to very good (schizotypal, antisocial, narcissistic, borderline κ=0.67-0.71) 37, 38 , comparing favorably with semi-structured interviews in clinical samples 67 .…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, there has been a historical belief that personality disorders, in contrast to clinical disorders, reflect enduring patterns that are relatively stable over time. Recent longitudinal studies, however, have demonstrated a natural plasticity of personality symptoms both in adulthood (Cohen, Crawford, Johnson, & Kasen, 2005;Lenzenweger, 1999;Livesley, 2005;Skodol et al, 2005;Zanarini, Frankenburg, Hennen, Reich, & Silk, 2005) & Verhulst, 2003). In addition, a mass of literature reports on the substantial overlap between personality and psychopathology in adults (Widiger, 2003) and children (Tackett, 2006), including shared genetic etiological factors (Bienvenu, Hettema, Neale, Prescott, & Kendler, 2007;Krueger, Markon, Patrick, & Iacono, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…22 Also, it seems that an impulsive act is a relatively stable aspect of BPD, but it is considered as a hypomanicdependent measure of BMD II. 23 According to the findings, the patients with BPD suffer from a higher degree of impulsive behavior and hostility, compared with the non-BPD patients. 24 Also, in another study it was concluded that the impulsive behavior in patients with BPD is distinct from that in the BMD II patients.…”
Section: Introductionmentioning
confidence: 99%